2020
DOI: 10.1177/1758835920920069
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RON receptor tyrosine kinase for treatment of advanced solid cancers: antibody–drug conjugates as lead drug candidates for clinical trials

Abstract: The recepteur d’origine nantais (RON) receptor tyrosine kinase, belonging to the mesenchymal-to-epithelial transition proto-oncogene family, has been implicated in the pathogenesis of cancers derived from the colon, lung, breast, and pancreas. These findings lay the foundation for targeting RON for cancer treatment. However, development of RON-targeted therapeutics has not gained sufficient attention for the last decade. Although therapeutic monoclonal antibodies (TMABs) targeting RON have been validated in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
(513 reference statements)
0
5
0
Order By: Relevance
“…Although monoclonal antibodies (mAbs) can have fewer off-target effects, our data suggests that mAbs that target FL-Ron may not be effective for immunotherapy. Indeed, poor efficacy of anti-Ron mAbs like narnatumab and others in clinical and preclinical studies (29,33,92) may be due to their inability to block SF-Ron. Our data warrants clinical investigations using small-molecule Ron kinase inhibitors that inhibit SF-Ron signaling, perhaps in combination with immunotherapy, for the prevention and treatment of metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although monoclonal antibodies (mAbs) can have fewer off-target effects, our data suggests that mAbs that target FL-Ron may not be effective for immunotherapy. Indeed, poor efficacy of anti-Ron mAbs like narnatumab and others in clinical and preclinical studies (29,33,92) may be due to their inability to block SF-Ron. Our data warrants clinical investigations using small-molecule Ron kinase inhibitors that inhibit SF-Ron signaling, perhaps in combination with immunotherapy, for the prevention and treatment of metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of wild-type RON overexpression in cancerous tissue was in primary breast cancer samples. Thereafter, IHC staining has further detected wild-type RON in thyroid, bladder, adrenal gland, head and neck, uterus, skin, lung, kidney, pancreatic, colorectal, and other tumors[ 59 ]. These findings are consistent with the results found in other cancers, such as human gliomas, melanoma, and Merkel cell carcinoma, suggesting that aberrant RON expression is also associated with both neurological and skin cancers[ 18 ].…”
Section: Aberrant Ron Signaling and Expression In Cancer Pathogenesismentioning
confidence: 99%
“…To generate RON-targeted ADCs, the anti-RON monoclonal antibodies PCM5B14 and Zt/g4 were selected to prepare immunotoxins. To generate Zt/g4 and PCM5B14-based ADCs, cytotoxic payloads with different mechanisms of action were conjugated, including pyrrolobenzodiazepine, duocarmycin (DCM), monomethyl auristatin E, and maytansinoid derivative 1, forming for example, Zt/g4-MME and PCM5B14-DCM[ 59 ]. Preclinical studies identified Zt/g4- and PCM5B14-based ADCs as lead candidates for clinical development and increased the chance of their entering into clinical trials (Table 1 ).…”
Section: Ron As a Therapeutic Target For Hbp Cancersmentioning
confidence: 99%
“…Previous studies show that aberrant RON expression and activation is achieved through overexpression of wild-type RON or generation of alternatively spliced RON variants harboring deletions, such as RON Δ155, Δ160, and Δ165, leading to constitutive receptor activation . In particular, RON splice variants naturally exist, and are tumorigenic, in numerous types of cancers, including colorectal cancer, non-small cell lung cancer (NSCLC), pancreatic cancer, and cholangiocarcinoma. Aberrant RON expression and activation is also prognostic of patient survival in a number of cancers. Such observations suggest the investigation of RON splice variants as cancer therapeutic targets. , However, although a number of RON inhibitors, such as carbozantinib ( 1 ), crizotinib ( 2 ), AMG-1 ( 3 ), BMS-777607 ( 4 ), and LY2801653 ( 5 ), have been well reported (Figure ), most currently known RON inhibitors only inhibit activation of the full-length protein. To the best of our knowledge, drugs targeting RON splice variants are not yet known, , with no reports of the DFG (Asp-Phe-Gly motif)-out conformation structure, and there is a lack of crystal structures of RON splice variants in the Protein Data Bank (PDB).…”
mentioning
confidence: 99%
“…8−10 Such observations suggest the investigation of RON splice variants as cancer therapeutic targets. 11,12 However, although a number of RON inhibitors, such as carbozantinib (1), crizotinib (2), AMG-1 (3), BMS-777607 (4), and LY2801653 (5), have been well reported (Figure 1), 13−17 most currently known RON inhibitors only inhibit activation of the full-length protein. To the best of our knowledge, drugs targeting RON splice variants are not yet known, 18,19 with no reports of the DFG (Asp-Phe-Gly motif)-out conformation structure, and there is a lack of crystal structures of RON splice variants in the Protein Data Bank (PDB).…”
mentioning
confidence: 99%